2011
DOI: 10.4103/0973-029x.80014
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysmal bone cyst of the mandible: A case report and review of literature

Abstract: Aneurysmal bone cyst (ABC) is rare benign lesions of bone which are infrequent in craniofacial skeleton. ABC’s are characterized by rapid growth pattern with resultant bony expansion and facial asymmetry. We describe a case of ABC in a 25 year old male patient affecting the body of the mandible with expansion and thinning of the buccal and lingual cortical plates. Treatment consisted of surgical curettage of the lesion. A one year follow- up showed restoration of facial symmetry and complete healing of the inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Presence of giant cells and histiocytes adherent to stromal fragments in a young female with normal serum calcium, parathyroid hormone and phosphorus levels is strongly suggestive of CGCG ( 3 ). ABC is a non-neoplastic and non-odontogenic cyst, accounting for <2% cases in jaw bones ( 16 ). Radiological appearance of an eccentric, unilocular, radio lucent lesion with cortical expansion though suggestive of ABC, is not pathognomonic, and needs to be confirmed on histopathology ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presence of giant cells and histiocytes adherent to stromal fragments in a young female with normal serum calcium, parathyroid hormone and phosphorus levels is strongly suggestive of CGCG ( 3 ). ABC is a non-neoplastic and non-odontogenic cyst, accounting for <2% cases in jaw bones ( 16 ). Radiological appearance of an eccentric, unilocular, radio lucent lesion with cortical expansion though suggestive of ABC, is not pathognomonic, and needs to be confirmed on histopathology ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…ABC is a non-neoplastic and non-odontogenic cyst, accounting for <2% cases in jaw bones ( 16 ). Radiological appearance of an eccentric, unilocular, radio lucent lesion with cortical expansion though suggestive of ABC, is not pathognomonic, and needs to be confirmed on histopathology ( 16 ). Role of cytology in the diagnosis of giant cell lesions of jaw has been mentioned by few authors ( 4 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Simple curettage is associated with high recurrence but few authors have reported no recurrence following simple curettage of mandibular lesion. [117]…”
Section: Discussionmentioning
confidence: 99%
“… 5 From a histopathological point of view, ABC can be classified into three types: conventional (vascular) type, which is a rapidly growing, extensive, damaging lesion, leading to cortical breach and soft tissue aggression; solid type, and a third mixed type of the other two types. 6 …”
Section: Introductionmentioning
confidence: 99%
“… 7 Magnetic resonance imaging scans regularly show an extensive tumour with eccentric osteolysis and a polylobulated aspect with fluid-fluid levels. 6 The differential diagnosis for an aneurysmal cyst can be essential bone cyst, giant cell tumour, osteoblastoma, and telangiectatic osteosarcoma. 2 A biopsy is mandatory for an aneurysmal cyst because telangiectatic osteosarcoma needs to be considered as a differential diagnosis.…”
Section: Introductionmentioning
confidence: 99%